Faktor-Faktor Penggerak Penerimaan Pajak Orang Pribadi di KPP Pratama Cilandak Jakata: Pemeriksaan Pajak, Kesadaran Wajib Pajak dan Surat Tagihan Pajak - Saragih, Muhammad Rizal; Rusdi, Rusdi (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Taxes are a crucial source of state revenue that plays an essential role in economic development. In Indonesia, efforts to increase tax revenue are continuously made through various policies and strategies. However, the level of taxpayer compliance remains a significant challenge for tax authorities, including at KPP Pratama Jakarta Cilandak. Therefore, this study aims to analyze the factors influencing tax compliance of taxpayers at KPP Pratama Jakarta Cilandak. This research adopts a quantitative approach with an associative research method. The study was conducted at KPP Pratama Jakarta Cilandak, with a population of 170,000 taxpayers. A sample of 100 respondents was selected using the Slovin formula, and a simple random sampling technique was applied. Data was collected through the distribution of questionnaires to the respondents, and the data was analyzed using multiple regression analysis. The findings show a positive and significant influence of the tested factors, such as taxpayer awareness, supervision level, and service quality, on tax compliance at KPP Pratama Jakarta Cilandak. The implications of these findings highlight the importance of enhancing taxpayer awareness, supervision, and service quality at KPP Pratama Jakarta Cilandak to encourage higher tax compliance in the future.